655.RELATIONSHIP BETWEEN THERMAL POLLUTION AND IMPACT OF OUTLET ANGLE OF THE THERMAL DISCHARGE - Milica, Jovčevski; Mirjana, Laković; Filip, Stojkovski; Milica, Ivanović (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2022)
Predicting the behavior of thermal discharges from power plants under different outlet angles of the thermal discharge was done. The operation of power plant Nikola Tesla B was considered. This power plant has a once-through cooling system and uses the Sava River as a natural water cooling system. For numerical simulation, Ansys Fluent software package was used. Five positions of the channel discharge angle were considered. A two-dimensional model was developed and the k-ε turbulence model was applied. During the analysis, the values of maximum temperatures generated by pouring the discharge channel were considered. Also, the size of the field affected by this type of pollution was observed. The obtained data as a result of numerical simulation can be used to study problems associated with the mixing of heated water discharged from thermal power plants into the river flow. With this study, it is possible to reduce the impact of thermal pollution from the power plant by selecting an adequate outlet angle for the thermal discharge channel.